Exploring motivation to notify and barriers to partner notification of sexually transmitted infections in South Africa - Wood, Julia M (Department of Public Health and Family Medicine, 2018)
Objectives: This article will review qualitative data from intervention-based counselling sessions to explore barriers to partner notification for men and women who have contracted sexually transmitted infections (STIs) in a township community in South Africa. It will further assess the intervention's impact on participants' motivation and skills to notify their partners about their STI status. Methods: Relying on recorded counselling sessions from an intervention run by a parent study, this substudy reviewed 30 transcripts from enhanced counselling sessions with 15 men and 15 women. Participants were adults between the ages of 19-41 (mean age = 28.4) who live within the catchment area of a South African township. Recordings were chosen based on verbal responsiveness of the participant and were manually coded for analysis. In addition, two programme counsellors were interviewed to enhance rigour and to reduce potential bias. Results: By the conclusion of the intervention session, both male and female participants were motivated to notify their partners face-to-face about their positive STI status. Despite this, misperceptions about the etiology and transmission of STIs, as well as inadequate support from the clinical level and power imbalances amongst men and women emerged as major barriers for the prevention of future STIs. Conclusions: While the intervention appears to be successful in facilitating partners' intentions to notify, the data shows significant social and structural barriers that will create difficulties for the prevention of future STIs. Participants' persistent concerns about acquiring HIV or their current positive status affect decision-making and therefore, could be a window of opportunity for health-care providers or lay counsellors to discuss STIs in high prevalence areas.